The Impact of Digital Marketing and Entrepreneurial Capabilities on Marketing Performance - Hardiansyah, Rian; Fahlia, Fahlia; Nuramaliyah, Nuramaliyah (Indonesian Business Review, 2024)
The objective of this study is to assess the impact of digital marketing and entrepreneurial competence on the marketing performance of micro, small, and medium enterprises (MSMEs) in the Sumbawa district. An investigation was carried out involving 180 owners of Micro, Small, and Medium Enterprises (MSMEs), and the collected data was evaluated using Structural Equation Modeling-Partial Least Square (SEM-PLS). The research findings indicate that both digital marketing competency and entrepreneurial competency have a notable and beneficial impact on marketing performance. Additionally, it is observed that digital marketing competency specifically has a favorable and considerable influence on marketing performance. According to the findings of this study, it is crucial for MSMEs in Sumbawa Regency to give priority to enhancing their digital marketing and entrepreneurial abilities in order to enhance their marketing effectiveness. This research has significant ramifications for owners of micro, small, and medium enterprises (MSMEs), policymakers, and researchers, highlighting the necessity for additional investigation into this subject matter.